UJI BEBERAPA KONSENTRASI EKSTRAK TEPUNG AKAR TUBA (Derris elliptica Benth.) TERHADAP MORTALITAS LARVA Helicoverpa armigera Hubner (Lepidoptera: Noctuidae) HAMA PADA JAGUNG MANIS - Mukhlis Ibrahim; Rusli Rustam (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2020)
Corn is one of the important food crops besides rice. The variety of corn that is in great demand by the public is sweet corn (Zea mays saccharata Sturt). The main pest that often attacks sweet corn plants is Helicoverpa armigera Hubner. Pest control can be carried out using botanical insecticides of tuba roots (Derris elliptica benth.). This research aims to obtain a concentration of tuba root flour extract which was effective against Helicoverpa armigera Hubner. The research was conducted at the Plant Pest Laboratory and Organic Chemistry and Natural Material Laboratory, Faculty of Engineering, Riau University. It was started from January to March 2020. This research used a completely randomized design (CRD) with five treatments and four replications so that 20 experimental units were obtained. The treatments given were various concentrations of tuba root flour extract, namely: 0%, 0.25%, 0.50%, 0.75% and 1%. The results showed that the difference in the concentration of tuba root flour extract had a significant effect on killing Helicoverpa armigera larvae. The concentration of 0.75% is effective in controlling Helicoverpa armigera larvae because it has been able to kill Helicoverpa armigera by 85% with the fastest initial death time at 3.75 hours, lethal time 50 at 17.00 hours after application.